Dependence of the g-Factor of Mineral Coals on a Metamorphism Level - G. Shilagardy,; P. Tuvshintur,; S. V. Adashkevich,; V. S. Kiranov,; N.M. Lapchuk,; I.V. Sedkova,; V.F Stelmach,; G.D. Frolkov,; Ts. Nyamdulam,; R. Khandmaa, (Scientific transaction of the National University of Mongolia. Physics, 2022)
Dependence of the g-Factor of Mineral Coals on a Metamorphism Level